REACAO DO TECIDO CONJUNTIVO SUBCUTANEO E DE FERIDAS INCISAS EM CONTACTO COM GAZE FURACINADA. ESTUDO HISTOLOGICO - De Carvalho, A. C.P.; Okamoto, T.; Callestini, E. A. (My University, 1979)
Strips of gauze and furacin gauze were implanted into the subcutaneous space and employed as dressing of dorsal incisions of albino rats. The animals were sacrificed after 24 hours, 2, 5, and 7 post-operative days. The pieces were processed for histological examination. It is possible to conclude that furacin gauze provokes more severe inflammatory reactions and does not favour connective neoformation and epithelization. Furacin gauze should be utilized only as a germicidal aim.
Reactions of subcutaneous connective tissue and incised wounds to strips of furacin gauze. Histologic study